Battles and leaders of the Civil War. - Cozzens, Peter, 1957- (University of Illinois Press, 2004)
The first four volumes of Battles and Leaders of the Civil War, published in the late nineteenth century, became the best-selling and most frequently cited works ever published on the Civil War. Volume 6 (like Volume 5), assembled by the acclaimed military historian Peter Cozzens, carries on the tradition of its namesake, offering a dazzling new collection of articles written by military and civilian leaders, North and South, on a broad array of war-related topics. Sifting carefully through reports from newspapers, magazines, personal memoirs, and letters, Peter Cozzens's Volume 6 brings readers more of the best first-person accounts of marches, encampments, skirmishes, and full-blown battles, as seen by participants on both sides of the conflict. Alongside the experiences of lower-ranking officers and enlisted men are accounts from key personalities including General John Gibbon, General John C. Lee, and seven prominent generals from both sides offering views on "why the Confederacy failed." This volume includes one hundred twenty illustrations, including sixteen previously uncollected maps of battlefields, troop movements, and fortifications. - Back cover.